Recasting Transnationalism Through Performance - McMahon, C. author. aut Link
XV, 229 p.
Keywords: A rigorous ethnography of three international theatre festivals spanning the Portuguese-speaking world, this book examines the potential for African theatre artists to generate meaningful cultural and postcolonial dialogues in festival venues despite the challenges posed by a global arts market.